2020
DOI: 10.1016/j.isci.2020.100944
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Achieving Balance between Detonation Performance and Crystal Stability of High-Energy-Density Materials

Abstract: Performance-stability contradiction of high-energy-density materials (HEDMs) is a long-standing puzzle in the field of chemistry and material science. Bridging the gap that exists between detonation performance of new HEDMs and their stability remains a formidable challenge. Achieving optimal balance between the two contradictory factors is of a significant demand for deep-well oil and gas drilling, space exploration, and other civil and defense applications. Herein, supercomputers and latest quantitative comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 117 publications
(58 reference statements)
3
20
0
Order By: Relevance
“…Pearson correlation coefficients listed in Table S4 indicate that the presence of gaseous N 2 in the reaction products is also important to detonation properties. These results are consistent with our recent knowledge-driven findings ( Li et al., 2020a , 2020b , 2020c ) that the generation of large amount of CO 2 and N 2 gas is conducive to the improvement of Q max , D , and p C-J of HEDMs. Furthermore, it was found that molecules, with high MW value and energetic rings connected via bridge bonds or with non-planer heterocyclic or cage-like backbones, are responsible for the better Q max of these molecules, whereas they have only a minimal influence on D and p C-J ( Figure S27 ; Supplemental information ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Pearson correlation coefficients listed in Table S4 indicate that the presence of gaseous N 2 in the reaction products is also important to detonation properties. These results are consistent with our recent knowledge-driven findings ( Li et al., 2020a , 2020b , 2020c ) that the generation of large amount of CO 2 and N 2 gas is conducive to the improvement of Q max , D , and p C-J of HEDMs. Furthermore, it was found that molecules, with high MW value and energetic rings connected via bridge bonds or with non-planer heterocyclic or cage-like backbones, are responsible for the better Q max of these molecules, whereas they have only a minimal influence on D and p C-J ( Figure S27 ; Supplemental information ).…”
Section: Resultssupporting
confidence: 93%
“…Pearson correlation coefficients presented in Table S4 ( Supplemental information ) indicate that the contribution of the presence of gaseous H 2 O in the products is negative for obtaining large value of Q max , and the contribution of the presence of solid C in the products has also negative effect on obtaining large values of D and p C-J . These results are consistent with the recent finding ( Li et al., 2020a , 2020b , 2020c ) that high proportion of H 2 O in the products leads to a lower Q max and high content of solid carbon clusters in the detonation products, which are obtained due to the oxygen deficiency in the structure of an HEDM, leads to a drastic decrease in D and p C-J of HEDMs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations